English Communication Skills in Tourism Improved with the Cooperative Project-Based STEAM Learning Model - Kristiana, Vera (IKIP Siliwangi, 2026)
English communication skills are a crucial competency for tourism students in response to the growing demands of the global tourism industry. Nevertheless, many students continue to experience challenges in using English effectively for professional purposes. This research aims to examine the enhancement of tourism students’ English communication skills through the application of a Cooperative Project-Based STEAM learning model. A quasi-experimental research design was employed, involving tourism students as participants. Data were gathered through English communication skill assessments, observation checklists, and questionnaires. The instructional activities were carried out through cooperative group projects that integrated Science, Technology, Engineering, Arts, and Mathematics (STEAM) elements into authentic tourism-related tasks. The findings reveal that students’ English communication skills especially in terms of speaking fluency, vocabulary mastery, self-confidence, and collaborative abilities showed significant improvement following the implementation of the learning model. In addition, students demonstrated positive attitudes toward cooperative and project-based learning. Therefore, it can be concluded that the Cooperative Project-Based STEAM learning model effectively enhances English communication skills in tourism education and may serve as an alternative approach in English language instruction.